Characterization and Function of 3-Hydroxy-3-Methylglutaryl-CoA Reductase in Populus trichocarpa: Overexpression of PtHMGR Enhances Terpenoids in Transgenic Poplar - Wei, Hui; Xu, Chen; Movahedi, Ali; Sun, Weibo; Li, Dawei; Zhuge, Qiang (Frontiers in Plant Science, 2019)
In the mevalonic acid (MVA) pathway, 3-hydroxy-3-methylglutaryl-CoA reductase (HMGR) is considered the first rate-limiting enzyme in isoprenoid biosynthesis. In this study, we cloned a full-length cDNA from Populus trichocarpa with an open reading frame of 1734 bp. The deduced PtHMGR sequence contained two HMG-CoA motifs and two NADPH motifs, which exhibited homology with HMGR proteins from other species. Subsequently, truncated PtHMGR was expressed in Escherichia coli BL21 (DE3) cells, and enzyme activity analysis revealed that the truncated PtHMGR protein could catalyze the reaction of HMG-CoA and NADPH to MVA. Relative expression analysis suggests that PtHMGR expression varies among tissues and that PtHMGR responds significantly to abscisic acid (ABA), NaCl, PEG6000, hydrogen peroxide, and cold stresses. We used PCR analysis to select transgenic Nanlin 895 poplars (Populus×euramericana cv), and qRT-PCR showed 3-10 fold higher expression levels of PtHMGR in transgenic lines than that in WT poplars. qRT-PCR was used to determine the transcript levels of methylerythritol phosphate (MEP)-, MVA-, and downstream-related genes, indicating that overexpression of PtHMGR not only affects expression levels of MVA-related genes, but also those of MEP-related genes. Furthermore, we measured the contents of terpenoids including ABA, gibberellin acid (GA), carotenes, and lycopene. Overexpression of PtHMGR significantly increased the contents of ABA, GA, carotenes, and lycopene, indicating that PtHMGR well participates in the regulation of terpenoid compounds synthesis.